Analisys of Tensile Strength, Wear Rate, and Cristallinity of Biocomposite Nano-HA/Magnesium/Shellac Reinforced Cantula Fiber for Bone Screw Material - Dea Pawestry Utami; Joko Triyono; Wijang Wisnu Raharjo; Rachmad Imbang Tritjahjono (Mekanika)
Accidents are a major cause of fractures in Indonesia. One of the treatments for fractures is bone screws with support plates that are placed on broken bone. Currently, many biomaterials for bone screws are being developed which have biodegradable properties so that post-operative bone healing is not required. The purpose of this study was to determine the effect of cantula fiber addition on tensile strength, wear rate, and crystallinity of nano-HA/magnesium/shellac bio-composite for bone screw materials. Nano-HA/magnesium/shellac/cantula fiber materials were mixed using a blender. The material was mixed with a magnesium/hydroxyapatite ratio of 70/30 and cantula fiber was added with variations of 0%, 10%, 20% and 30% of total volume. After that, material mixture was compacted with a pressure of 300 MPa for 10 minutes. Then sintering process was carried out at temperature of 140 °C for two hours. The results showed that the highest tensile strength value was 7.86 MPa at 30% variation. The lowest wear rate was 0.31 x 10-3 mm3/Nm at 30% variation. The highest crystallinity in X-Ray Diffraction observations was obtained at 30% variation, which was 79.65%.